Soil Characteristics, Growth, Yield, Mineral Composition and Proximate Content of Soybeans Under Various Tillage Techniques - Aruna Olasekan Adekiya; Olajire Damilola Adedokun; Ojo Timothy Adebiyi (International Journal of Agronomy)
Different tillage methods can have varying effects on soil properties and crop quality. Therefore, field experiments were conducted at the Teaching and Research Farm of Landmark University, located in Omu-Aran, Kwara State. The objectives were to investigate the impacts of various tillage methods on soil characteristics and the growth, yield, mineral and proximate content of soybean (Glycine max (L.) Merr.). Based on these objectives, it was hypothesized that soil properties, growth, yield, mineral and proximate contents of soybean would react differently to different tillage methods. Consequently, experiments were conducted to validate this hypothesis. The treatments were four tillage methods: manual clearing (MC), ploughing (P), ploughing plus harrowing (P + H) and manual ridging (MR), replicated three times in a randomized complete block design. Data on the initial soil properties (bulk density, particle size, pH, organic matter, N, P, K, Ca and Mg), along with the chemical properties of the soil on a per-plot basis at the end of the experiment, were collected. Additionally, data on soil bulk density, porosity, moisture content and temperature were collected during the vegetative growth of the soybean. Soybean plant height and the number of branches were recorded at the midflowering stage, while grain yield and the number of pods were recorded at harvest. Soybean seeds were later analysed for their mineral and proximate contents using standard methods. P + H resulted in lower soil bulk density than other tillage methods and led to higher growth, yield, proximate and mineral contents of soybean. In MC, bulk density, soil moisture content, soil organic matter, N, P, K, Ca and Mg were significantly higher and temperature lower than in other tillage methods; yet, these advantages did not translate into increased yield and quality due to the higher bulk density. The growth, yield and quality of soybean were significantly influenced by soil bulk density rather than by soil chemical properties. Using the mean of the two sites, relative to MC, P and MR, P + H increased the grain yield of soybean by 41.3%, 24.4% and 13.7%, respectively. These findings underscore the importance of appropriate tillage practices for successful soybean cultivation in similar agroecological zones. For small-scale operations, MR is suggested, while P + H is recommended for large-scale soybean production in the studied area. Future studies could include additional variables, such as economic analysis, long-term soil health impacts or the effects of tillage methods under varying climate conditions.